El proyecto hidroeléctrico de Arenal y el impacto en su entorno económico y social (1950-1994) - Hilje Quirós, Brunilda (1997)
The author analyzes the impact of the construction of the Arenal hydroelectric project, and uses oral history to uncover the opinion of those peasants whose lands were flooded by the dam´s construction.